2007
DOI: 10.1590/s1677-04202007000200005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of iron on mineral status of two rice (Oryza sativa L.) cultivars

Abstract: Iron is an essential nutrient for plants. In aerobic conditions, Fe is highly unavailable for plant uptake, and Fe deficiency can be severe in plants grown in calcareous soils. In waterlogged soils, however, Fe availability increases and can reach toxic concentrations. Rice is an important staple crop worldwide and faces iron deficiency or excess, depending on the growth conditions. To contribute to the study of mechanisms involved in response to Fe deficiency and resistance to Fe excess, experiments were carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
47
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 47 publications
(47 reference statements)
9
47
1
4
Order By: Relevance
“…First, Fe, Zn, Cu and Ni were preferentially accumulated in roots. Silveira et al (2007) also detected higher Fe levels in roots than in shoots of different rice cultivars. Fe is mainly required for photosynthesis, respiration, sulphate assimilation, hormone synthesis, nitrogen fixation, as well as DNA synthesis and repair (Puig et al, 2007;Sperotto et al, 2010).…”
Section: Growth and Mineral Dynamics -Single Elementmentioning
confidence: 84%
“…First, Fe, Zn, Cu and Ni were preferentially accumulated in roots. Silveira et al (2007) also detected higher Fe levels in roots than in shoots of different rice cultivars. Fe is mainly required for photosynthesis, respiration, sulphate assimilation, hormone synthesis, nitrogen fixation, as well as DNA synthesis and repair (Puig et al, 2007;Sperotto et al, 2010).…”
Section: Growth and Mineral Dynamics -Single Elementmentioning
confidence: 84%
“…Seemingly, E108 plants were able to restrict Fe accumulation, reaching lower shoot Fe concentrations when submitted to Fe overload than the I409 plants. Silveira et al (2007) had already suggested that E108 plants rely mostly on avoidance of Fe uptake into the plant and decreased translocation to shoots when coping with Fe overload. Based on results herein presented, we suggest that the tolerance mechanism to excess Fe in E108 includes both restricted Fe translocation and increased ferritin accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…indica) seeds from cultivars EPAGRI 108 (E108) and BR-IRGA 409 (I409) were provided by IRGA (Instituto Rio Grandense do Arroz, Brazil). These cultivars have been previously characterized as tolerant and susceptible to Fe toxicity (Nava & Bohnen, 2002;Silveira et al, 2007). After germination and growth in vermiculite and nutrient solution (Yoshida et al, 1976) for 14 days in an incubator (28°C, first two days in the dark and remaining days with 16 h of light), plants were transferred to glass pots covered with aluminum foil and containing 500 mL of nutrient solution.…”
Section: Plant Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Fe toxicity in leaves causes necrotic spots, dark roots, inhibition of plant growth (Dobermann and Fairhurst 2000) and cationic unbalance, which promotes nutritional imbalances. In rice, excess of Fe has resulted in a reduction in the absorption of P, K, Ca and magnesium (Mg) (Silveira et al 2007). In Beta vulgaris under the effects of Fe toxicity, changes in chloroplast structure were observed, with reduced numbers of grana and stromal lamellae per chloroplast, and of thylakoids per grana, and also reduced numbers of P 700 molecules and cytochrome f per unit of area.…”
Section: Ecophysiological Responses To Iron Toxicitymentioning
confidence: 99%